Cardiac anxiety in the perioperative period of patients undergoing cardiac surgical procedures: an observational study - Kazitani,Bruna Sonego (2023)
ABSTRACT Objective: to compare cardiac anxiety symptoms in patients undergoing coronary artery bypass graft and valve surgery repair in the preoperative period, on the day of hospital discharge and on the first return visit after hospital discharge. Methods: an observational study, carried out in inpatient units and in outpatient clinic of a university hospital. Data were collected through interviews. Cardiac anxiety symptoms were assessed using the Cardiac Anxiety Questionnaire. Results: we observed the effect of time on cardiac anxiety symptoms of patients undergoing coronary artery bypass graft in the total score and in the “Avoidance” domain at discharge and at the first return visit. In patients undergoing valve repair surgery, the effect of time on symptoms was observed only in the first return visit, when compared with the preoperative period. Conclusion: the findings revealed increased cardiac anxiety symptoms in the postoperative period, discharge and first return, when compared to the preoperative period.